The Influence of Supply Chain Management on the Economic Dynamics of the Region in Comparison with Traditional Factors - Marat Rashitovich Safiullin; Alexander Stanislavoich Grunichev; Alia Aidarovna Abdukaeva (International Journal of Supply Chain Management, 2020)
Abstract— The paper substantiates the need to study issues that discover the features of the influence of region’s supply chain management on its macroeconomic dynamics through the prism of economic and mathematical analysis. This will allow us to form a new vector for constructing models of economic growth and to localize an inclination of applying qualitative methods of analysis in this area of research towards quantitative approaches to the analysed processes and phenomena. In this regard, the main goal of this work is to develop methodological tools to assess the impact of supply chain management on the dynamics of regional economic growth, as well as to form mechanisms for a comparative analysis of the influence of the region’s reputation with traditional factors that activate macroeconomic generation. The Republic of Tatarstan acts as an object of study. The subject of the study is a methodological toolkit for assessing the impact of a region’s reputation on the parameters and dynamics of investment processes. A key feature of the study is the proposed version of the comparative analysis of traditional and non-traditional factors (the latter include supply chain management in this work) that trigger mechanisms of investment growth in the regional economic system. On the basis of the developed methodology for the formalized assessment of the region’s supply chain management, the authors have constructed models that evaluate the level of the comparative impact of reputation on the processes of generating investments in fixed assets. It is advisable to use the developed methodological approaches when developing new models of economic growth under conditions of increased importance and the role of intangible production factors. According to the results of the study, we have proved that the region’s supply chain management plays one of the leading roles along with traditional basic factors that trigger the mechanisms of intensification of investment activity. Moreover, as the calculations show, the importance of reputation for the matter of activating investment processes is even slightly more noticeable than such an important indicator as the “Balanced financial result of economic entities”..